Leader humility and organisational citizenship behaviour: the mediating roles of job satisfaction and employee engagement - Abraham Ansong; Sylvester Ansah Owusu; Linda Obeng Ansong; Raphael Papa Kweku Andoh (Cogent Business & Management, 2024)
The study examined leader humility (LH) and organisational citizenship behaviour (OCB) with the mediating roles of job satisfaction (JS) and employee engagement (EE) among employees in a public university in Ghana. A cross-sectional research design was used in carrying out the study. The study used stratified sampling to sample 246 respondents and data garnered using a questionnaire while structural equation modelling was utilised in testing the hypotheses. This study demonstrated that LH has a positive and significant relationship with OCB, JS and EE. The results of the study further showed that JS and EE have significant positive link with OCB. Finally, the study established that JS and EE played partial mediation roles in the link between LH and OCB. The results of this study indicate that employees whose supervisors have humble leadership traits tend to be satisfied, engaged and ultimately, are able to exhibit OCB. This implies that humble leaders are assets to their organisations. Thus, organisations seeking to have satisfied and engaged employees as well as employees who indulge in OCB should ensure that their supervisors have humble leadership traits.
Keywords: 650; humble leadership; extra-role behaviour; work engagement; job satisfaction; family supportive supervisor behaviour; trust in supervisor